Specific Physiological and Anatomical Traits Associated With Polyploidy and Better Detoxification Processes Contribute to Improved Huanglongbing Tolerance of the Persian Lime Compared With the Mexican Lime - Sivager, Gary; Calvez, Leny; Bruyere, Saturnin; Boisne-Noc, Rosiane; Brat, Pierre; Gros, Olivier; Ollitrault, Patrick; Morillon, Raphaël (Frontiers in Plant Science, 2021)
Huanglongbing (HLB) is presently a major threat to the citrus industry. Because of this disease, millions of trees are currently dying worldwide. The putative causal agent is a motile bacteria belonging to Candidatus Liberibacter spp., which is transmitted by psyllids. The bacteria is responsible for the synthesis of callose at the phloem sieve plate, leading to the obstruction of the pores that provide connections between adjacent sieve elements and, thus, limiting the symplastic transport to the other plant organs of the sugars and starches synthesized in leaves. The Persian triploid lime (Citrus latifolia) is one of the most HLB-tolerant varieties of citrus, but the determinants associated to the tolerance are still not known. The diploid Mexican lime (C. aurantiifolia) and Persian lime were investigated when infected by HLB. The leaf petiole was analyzed using Scanning Electron Microscopy (SEM) to observe callose deposition at the phloem sieve plate. Leaf starch contents and detoxification enzyme activities were investigated. In the field, Persian lime leaves present more limited symptoms due to HLB than the Mexican lime. Photosynthesis, stomatal conductance, and transpiration decreased compared with control plants, but values remained greater in Persian than in Mexican limes. Analysis of the petiole sieve plate in control petiole samples showed that pores were approximately 1.8 fold larger in Persian than in Mexican limes. SEM analysis of petiole samples of symptomatic leaves showed important deposition of callose into pores of Mexican and Persian limes, whereas biochemical analysis revealed better detoxification in Persian lime than in Mexican lime. Moreover, SEM analysis of infected petiole samples of asymptomatic leaves showed much larger callose deposition into the Mexican lime than in the Persian lime pores, whereas biochemical traits revealed much better behavior in Persian lime than in Mexican lime. Our results reveal that polyploids present specific behaviors that are associated with important physiological and biochemical determinants that may explain the better tolerance of the Persian lime against HLB compared with the Mexican lime.